Importance Of Diet (Pathya- Apathya ) In Madhumeha- A Review Article - Geetika; Pandey, Punita; Tewari, Priya ranjan (International Research Journal of Ayurveda & Yoga, 2021)
According to Ayurveda , the main aim is to maintain health of a person and cure an existing disease. Maintenance of health is done by following proper diet and regimes . In Ayurveda Acharayas has describe diet (Pathya- Apathya) for all the Vyadhis (diseases). Prameha (DM) is a Chirkari Vyadi (Chronic illness) and Yapana of Vyadhi (diseases) must be done with aid of Aushadha(medicine), Ahara (diet) and Vihara (Life style). Ahara (diet) and Vihara(Life style). are of same value as medicines, since Hetu of vyadhi (causative factor) originates in them. The diets are recommended for habitual intake is beneficial only if taken in appropriate quantity, quality and considering all criteria mentioned in selecting wholesome food in healthy person as mentioned in Ayurveda. Ayurveda considers appropriate diet in particular disease is as powerful as medicine. It is suggested in Swasthvrittha as a routine to maintain the proper health . Pathya kalpana (wholesome), must be used in Dincharya (Daily regimen) and Rutucharya (Seasonal regimen).